Effect of the time interval between denudation and ICSI on fresh embryo transfer reproductive outcomes: a retrospective study - Xiao, Li; Xue, Luqi; Zhang, Ju; Fan, Wei; Zhu, Huili; Huang, Wei (Frontiers in Endocrinology, 2024)
Purpose This study aims to determine if the incubation after oocyte denudation before Intra-cytoplasmic sperm injection (ICSI) affects the clinical pregnancy rate. Methods This was a retrospective, consecutive data analysis of 1370 patients who underwent ICSI cycles at the Department of Reproductive Medicine of West China Second University of Sichuan University (Chengdu, Sichuan) between January 2020 and July 2022. The primary outcome was the clinical pregnancy rate. The second outcome included fertilization rate, biochemical pregnancy rate, and miscarriage rates. Results A total of 1370 continuous fresh transferred ICSI cycles were analyzed. Multivariate linear regression and logistic regression analysis of factors related to clinical pregnancy rates revealed that clinical pregnancy rates were significantly associated with denudation (DEN)-ICSI time interval. Long DEN-ICSI intervals are associated with a higher clinical pregnancy rate during fresh embryo transfer. Conclusion The DEN-ICSI time interval is an independent factor for clinical outcomes in fresh ICSI transfer cycles.